Improved prognosis with additional medium‐dose VP16 to CY/TBI in allogeneic transplantation for high risk ALL in adults. Issue 1 (9th November 2017) - Arai, Yasuyuki; Kondo, Tadakazu; Shigematsu, Akio; Tanaka, Junji; Ohashi, Kazuteru; Fukuda, Takahiro; Hidaka, Michihiro; Kobayashi, Naoki; Iwato, Koji; Sakura, Toru; Onizuka, Makoto; Ozawa, Yukiyasu; et al.
Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) with the conventional cyclophosphamide and total body irradiation (CY/TBI) regimen is an essential therapeutic strategy for acute lymphoblastic leukemia (ALL) in adults. Medium‐dose etoposide (VP16, 30‐40 mg/kg) can be added to intensify this CY/TBI regimen and reduce relapse; however, differences in prognosis between the VP16/CY/TBI and CY/TBI regimens have not yet been fully analyzed. We conducted a retrospective cohort study using a Japanese transplant registry database to compare the prognosis between the VP16/CY/TBI (VP16, total 30‐40 mg/kg) ( N = 376) and CY/TBI ( N = 1178) regimens in adult patients with ALL transplanted at complete remission (CR) between January 1, 2000 and December 31, 2014. Our analyses indicated that VP16/CY/TBI significantly reduced relapse compared with CY/TBI (risk ratio, 0.75; 95% confidence interval [CI], 0.56‐1.00; P = .05) with a corresponding improvement in leukemia‐free survival (hazard ratio [HR], 0.76; 95%CI, 0.62‐0.93; P = .01), particularly in patients transplanted at CR1 with advanced‐risk (positive minimal residual disease, presence of poor‐risk cytogenetics, or an initial elevated leukocyte count) (HR, 0.75; 95%CI, 0.56‐1.00; P = .05) or those transplanted beyond CR2 (HR, 0.58; 95%CI, 0.39‐0.88; P = .01). The addition of VP16 did not increase post‐transplant complications or nonrelapse mortality (HR, 0.88; 95%CI, 0.65‐1.18; P = .38). This study is the first to reveal the efficacy of the addition of medium‐dose VP16 to CY/TBI in high‐risk ALL. To establish new myeloablative conditioning regimens including VP16, a large‐scale prospective study is necessary.